(untitled) (The International Journal for Scientific Research, 2024)
In light of the complex challenges currently facing humanity, including climate change, rapid population growth and global economic and political turmoil, it has become imperative to develop and implement effective strategies to address these issues. Project management (PM) represents a business solution to address complex issues, as well as to ensure the continuity and availability of resources for the future. Although the discipline of project management originated in the early 20th century, it has undergone continuous evolution in response to the evolving needs of business. The project management approach is contingent upon the nature of the issue being addressed and the complexity of the project. In order to achieve the greatest success, organizational leaders seek to align the project management style with the specific project in focus. The telecommunications sector plays a pivotal role as a platform for technological and management innovations. As the second most important sector in Yemen after the oil sector, the sustainability of this sector is of paramount importance in order to ensure tangible progress in the country’s development. This thesis examines the effectiveness of modern project management methodologies in promoting sustainability in this pivotal sector. This study employs a multi-method research design to collect quantitative data from 150 professionals in leading telecommunications companies. Additionally, it incorporates qualitative insights from 22 in-depth interviews with project managers and key stakeholders to evaluate the current state of the industry with regard to the strategies employed to manage telecommunications projects and ascertain whether these strategies facilitate sustainability in the sector. The analysis reveals a high level of familiarity and application of project management methodologies, including Waterfall, Agile. Some projects have adopted sustainable practices, such as energy efficiency, there is a lack of proper training, regulatory challenges.